Peran Pemimpin dalam Menjaga Kualitas Produk Minuman BPOM pada PT. Tirta Fresindo Jaya di Kabupaten Banyuasin - Heru Adi Putranto; Citra Lasha; Sunarto; A.Ridhuan Habena; Tetty Espriyanti Malau (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
As a beverage manufacturing company, PT. Tirta Fresindo Jaya (Mayora Indah Tbk Group) is required to consistently maintain product quality in accordance with Food and Drug Monitoring Agency (BPOM) standards to remain competitive and meet the industry's requirements. This study aims to determine the role of leaders in maintaining product quality and the factors that support the successful implementation of quality standards.The study employed a descriptive qualitative method, with data collection techniques including observation, interviews, documentation, and literature review. The research informants included the Production Unit Head, Production Operators, Production Administrators, and the public as consumers. The results indicate that leaders play a crucial role through planning, supervision, communication, reward provision, and prompt decision-making when quality issues arise. Leaders also foster a culture of quality and SOP compliance with BPOM standards. In conclusion, the success of maintaining product quality at PT. Tirta Fresindo Jaya is inseparable from effective, participatory leadership, and consistency in adhering to quality standards.